Gonzo capitalism : how to make money in an economy that hates you - Guillebeau, Chris (Little, Brown Spark, 2023)
"The traditional ways of earning a living are outdated, if not outright rigged. That's why a growing number of enterprising individuals are instead turning to the growing ecosystem of decentralized, fast-moving virtual markets to pursue a host of previously unheard-of ways to pay the bills. Join New York Times bestselling author Chris Guillebeau on a fascinating tour of this brave new world where novelty is currency, and the creators are in control. Along the way, you'll meet a colorful cast of renegades who are driving this money revolution"--